A Novel Channelopathy in Pulmonary Arterial Hypertension - Ma, Lijiang; Roman-Campos, Danilo; Austin, Eric D; Eyries, Mélanie; Sampson, Kevin S; Soubrier, Florent; Germain, Marine; Trégouët, David-Alexandre; Borczuk, Alain; Rosenzweig, Erika Berman; Girerd, Barbara; Montani, David; et al. (The New England journal of medicine, 2013)
In a family with pulmonary arterial hypertension, whole-exome sequencing led to identification of a mutation in the potassium-channel gene KCNK3 . Additional mutations resulting in loss of function of the channel were found in other families and in patients with idiopathic disease. Pulmonary arterial hypertension is a rare disease that is characterized by increased pulmonary-artery pressure in the absence of common causes of pulmonary hypertension, such as chronic heart, lung, or thromboembolic disease. 1 Before the advent of novel therapies, patients with idiopathic or familial pulmonary arterial hypertension had an estimated median survival of 2.8 years, with 1-year, 3-year, and 5-year survival rates of 68%, 48%, and 34%, respectively. 2 However, despite progress in treatment, pulmonary arterial hypertension remains a progressive, fatal disease. The clinical presentation can be nonspecific, and patients often receive a diagnosis late in their clinical course. The cause of pulmonary . . .